Survival analysis of early initiation of antenatal care visits and associated factors among pregnant women in Ethiopia. - Nuru Mohammed Hussen; Kindu Kebede Gebre; Tilahun Gemechu Rorisa; Mekash Ayalew Mohammed (PLoS ONE)
Introduction Early initiation of antenatal care visits creates an opportunity for early detection of high-risk pregnancies, pregnancy complications, health education, and counseling about successful care and nutrition of the mother and the fetus. Thus, the main objective of this study was to identify the factors associated with the early initiation of antenatal care visits in Ethiopia. Methods The study was conducted based on the children's data set of the 2019 Ethiopia mini-demographic and health survey. The study employed a retrospective cohort study design using the data downloaded from the Measure Demographic and Health Survey website. The study included a random sample of 2922 pregnant women who had complete information about their first antenatal care visits. A gamma-accelerated failure time model was employed to identify the factors associated with the early initiation of antenatal care visits in Ethiopia. Results In Ethiopia, 62% of the pregnant women started their first antenatal care visit early. The higher birth order of the current pregnancy (ϕ = 2.215, 95% CI: 1.8901, 2.5966), mothers being rural residents (ϕ = 1.239, 95% CI: 1.1633 1.3195), mothers aged 25-34 (ϕ = 1.692, 95% CI: 1.5588, 1.8369), and mothers aged above 34 (ϕ = 1.826, 95% CI: 1.6392, 2.0336) were associated with an accelerated time to initiation of antenatal care visits. However, mothers attained higher education (ϕ = 0.830, 95% CI: 0.7345, 0.9373) and rich wealth index (ϕ = 0.869, 95% CI: 0.8156, 0.9259) were associated with a shorter time to initiation of antenatal care visits. Conclusion A higher proportion of urban and educated pregnant women initiated their antenatal care visits earlier than the other groups. We recommend that stakeholders at the federal and regional levels should focus on providing special concern for information, education, and communication regarding the importance of early antenatal care visits initiation.